SODIUM–SULFUR AND SODIUM–SELENIUM BATTERIES OPERATING AT ROOM TEMPERATURE (Scientific journal of the Fergana State University, 2026)
Sodium-based secondary batteries, especially sodium–sulfur (Na–S) and sodium–selenium (Na–Se) systems, are attracting attention as future energy storage technologies due to their low cost and stability. This article reviews recent literature results on the chemical composition of carbonate and ether-based electrolytes for Na–S and Na–Se batteries, their modification strategies, and electrochemical performance. Approaches to electrolyte additives, ionic transport mechanisms, and electrode–electrolyte interphase stability are compared, and promising electrolyte design directions for these systems are discussed.